Lava lake activity at Nyiragongo volcano between the years 2020 and 2021 documented by seismic activity and sulfur dioxide emissions, DRC - Munguiko, Olivier; Maska, Solange; Habari, Faustin S.; Minani, Abel S.; Bakole, Eliode; Mavonga, Tuluka; Ngangu, Bonheur; Sadiki, Arsène T.; Balezi, Gentil (Volcanica, 2024)
The activity of Nyiragongo volcano was assessed based on seismic data and SO2 measurements during the years 2020 and 2021. We analysed several events that marked the activity of the Nyiragongo lava lake. It was found that when SO2 concentrations reached more than 9 kT/day, Nyiragongo is in intense activity. The high SO2 emission in the Nyiragongo gas plume generates LP and VLP earthquakes, the RSAM curve can decrease when intrusions occur. The RSAM may still increase after degassing of SO2 to reflect the influx of new magma. SO2 outgassing always precedes seismic activity (LP and VLP), except when the crater was empty, seismic activity (with LP and VLP) had started, but the RSAM increased with outgassing. This leads us to notice a close link between the seismo-volcanic activity and the SO2 emissions. Both tools are therefore essential for the monitoring of Nyiragongo volcano.